On the in vivo assessment of goblet cells of the human bulbar conjunctiva by confocal microscopy – A review - Doughty, Michael J. (Contact lens & anterior eye, 2020)
•Provides the first objective analysis of confocal assessments of conjunctival goblet cells.•Analyses reveal notable differences between studies that need to be addressed.•Differences between studies appear to be uniquely dependent on the strategies used for image selection. In vivo confocal microscopy (IVCM) has been used for over 10 years to assess the goblet cell density (GCD) within the human conjunctiva, but the reported values have been variable with no obvious indications as to why. From publications between 2008 and 2019, representative GCD values were extracted, as well as on the image sampling strategy used. Average GCD values for any particular group of individuals ranged from 7 to 979 goblet cells / sq. mm, and with one notable outlier removed, an overall group-mean value for GCD (+/− SD) from single site locations was 207 +/− 143 goblet cells / sq. mm from 15 data sets for those usually designated as control subjects, with a value of 190 +/− 161 goblet cells / sq. mm calculated from 20 single site data sets from other (patient) groups. An overall analysis indicated that the reported average values for GCD from different groups of individuals increased according to the number of images assessed / individual (Spearman rho = 0.304), on the number of individuals evaluated to generate an averaged value for each group (rho = 0.367), and the total number of images assessed (rho = 0.346, multivariate analysis partial r = greater or = to 0.522). In the use of confocal microscopy to assess the number of goblet cells in the human bulbar conjunctiva, the substantial differences reported appear to be linked to the protocols used for image selection, and some type of standardization needs to be developed.